The effects of socio-demographic factors on physical activity in gated and non-gated neighbourhoods in Karachi, Pakistan - Gul, Yasmeen; Sultan, Zahid; Moeinaddini, Mehdi; Jokhio, Gul A. (Routledge, 2019)
Physical activity (PA) is important in ensuring a healthy population. It is dependent on various socio-demographic (SD) factors, such as age, gender, employment and marital status. A limited number of studies have investigated the relationship between SD factors and PA but research exploring this relationship from the perspective of gated and non-gated neighbourhoods is scarcer. Therefore, the objective of this study is to investigate the relationship between SD factors and PA variables in gated and nongated neighbourhoods in Karachi Pakistan. Results of the independent sample t-test and Pearson chi-square showed that young and single people do more sports activities in gated neighbourhoods. Women, unemployed people and public transport users walk more in non-gated neighbourhoods. In conclusion, future neighbourhoods should have more pedestrian friendly areas and a larger number of PA facilities, rather than building more walls and gates.